Impact Analysis on Performance with Emotional Intelligence, Intellectual Intelligence, and Spiritual Intelligence (Case Study on Medical and Unmedical Performance at Telogorejo Hospital) - Cuk Jaka Purwanggono; Bima Hermastho (Universitas Wahid Hasyim Semarang, 2022)
This research aims to analyze and test intellectual intelligence, emotional intelligence, and spiritual intelligence on heart specialists' performance at Telogorejo Hospital. The qualitative approach was used with 51 people as primary data. Surveys as data collection are used by providing questionnaires that must be filled out by respondents. In this research, data has been analyzed through reliability tests, classical assumption tests, validity tests, and T-Test to prove research hypotheses with a software namely measured using the statistical package for the social sciences (SPSS) 16.0 tool. The result shows that the T-Test for heart specialists at the intellectual intelligence does not impact in negative -0,92 with a significance 0,927 toward performance. It aligns with emotional intelligence with -0,691 with a significance 0,493. In contrast with them, the spiritual intelligence effect is positive with 2,941 significance 0,005 in performance from heart specialist Telogorejo HospitalKey word : intellectuals intelligence; emotional intelligencel; spiritual intelligence; employee performance